2021
DOI: 10.3389/fimmu.2021.804870
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Intestinal Barrier Function Induced by Early Weaning via Autophagy and Apoptosis Associated With Gut Microbiome and Metabolites

Abstract: Early weaning piglet is frequently accompanied by severe enteric inflammatory responses and microbiota dysbiosis. The links between the gut microbiome and the etiology of gut inflammation are not fully understood. The study is aimed to investigate the potential molecular mechanisms mediating inflammatory reactivity following early weaning, and to find whether these changes are correlated with gut microbiota and metabolite signatures by comparison between suckling piglets (SPs) and weaning piglets (WPs). Histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…In addition, the alkaline phosphatase (AKP) in the small intestinal villus epithelium is a landmark key enzyme associated with intestinal digestion and absorption function, which helps to increase the uptake and transport rate of nutrients, and also converts adenosine diphosphate (ADP) into adenosine triphosphate (ATP) (24,26,60,61). Previous studies had demonstrated that early weaning significantly decreased small intestinal AKP activity in piglets (27,62,63), which indicated that weaning stress has adverse effects on intestinal digestion and absorption function. In conclusion, one possible explanation for the decrease of intestinal digestive enzymes activity in piglets caused by weaning may be due to the negative effect of weaning stress on intestinal morphology, which in turn inhibits the secretion of endogenous enzymes (51, 64, 65).…”
Section: Weaning Stress Inhibits the Secretion Of Intestinal Digestiv...mentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, the alkaline phosphatase (AKP) in the small intestinal villus epithelium is a landmark key enzyme associated with intestinal digestion and absorption function, which helps to increase the uptake and transport rate of nutrients, and also converts adenosine diphosphate (ADP) into adenosine triphosphate (ATP) (24,26,60,61). Previous studies had demonstrated that early weaning significantly decreased small intestinal AKP activity in piglets (27,62,63), which indicated that weaning stress has adverse effects on intestinal digestion and absorption function. In conclusion, one possible explanation for the decrease of intestinal digestive enzymes activity in piglets caused by weaning may be due to the negative effect of weaning stress on intestinal morphology, which in turn inhibits the secretion of endogenous enzymes (51, 64, 65).…”
Section: Weaning Stress Inhibits the Secretion Of Intestinal Digestiv...mentioning
confidence: 93%
“…In general, during the first 3 weeks after birth, the digestive system of piglets develops rapidly due to adequate nutrition intake from sows, and the activities of digestive enzymes such as intestinal lactase, protease, and lipase are significantly increased (53). However, due to the change in diet, the activities of enzymes on the brush border of the intestinal mucosa, such as disaccharidases, protease, and lipase are dramatically changed after weaning (27,31,38,54,55). It has been confirmed that intestinal morphology is associated with changes in intestinal digestive enzyme activities (14,27,32,56,57).…”
Section: Weaning Stress Inhibits the Secretion Of Intestinal Digestiv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study reported that the upregulation of TLR4, MyD88, and NF-κB was involved in lipopolysaccharide (LPS)-induced inflammatory injury through the enhanced production of pro-inflammatory cytokines including IL-1β, TNF-α, and IL-6 in the colonic mucosa of piglets ( Gao et al, 2021 ). Tang et al (2021) found that early weaning induced inflammation and impaired intestinal barrier function through the upregulation of TLR4, IL-1β, IL-6, and TNF-α in piglet colon. Pie et al (2004) also reported that weaning increased the expression of IL-1β, IL-6, and TNF-α in the mid-small intestine and up-regulated the expression of IL-1β in the proximal colon of piglets.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the change of diet and psychological and environmental conditions, weaned piglets may experience rapid stress and other uncomfortable reactions, which then lead to the occurrence of symptoms such as decreased appetite, poor digestion, intestinal inflammation, and intestinal microbiota disorders, which seriously affect the growth and healthy of piglets ( 1 , 2 ). The natural weaning time of piglets is usually about 17 weeks after birth; however, early-weaning measures at 21 days of age are commonly used in intensive pig farms ( 3 ). Early weaning helps to improve the reproductive performance of sows by shortening the estrus interval, shortens the slaughter time for pigs by promoting growth throughout the life cycle, improves the utilization of the pen, and reduces the risk of disease transmission from sows to piglets, thus significantly improving farming efficiency ( 4 ).…”
Section: Introductionmentioning
confidence: 99%